Visceral transplantation in patients with intestinal‐failure associated liver disease: Evolving indications, graft selection, and outcomes. Issue 6 (6th April 2018) - Hawksworth, Jason S.; Desai, Chirag S.; Khan, Khalid M.; Kaufman, Stuart S.; Yazigi, Nada; Girlanda, Raffaele; Kroemer, Alexander; Fishbein, Thomas M.; Matsumoto, Cal S.
Abstract : Intestinal failure (IF)‐associated liver disease (IFALD) is widely recognized as a lethal complication of long‐term parenteral nutrition. The pathophysiology of IFALD is poorly understood but appears to be multifactorial and related to the inflammatory state in the patient with IF. Visceral transplant for IFALD includes variants of intestine, liver, or combined liver–intestine allografts. Graft selection for an individual patient depends on the etiology of IF, abdominal and vascular anatomy, severity of IFALD, and potential for intestinal rehabilitation. The past decade has witnessed dramatic improvement in the management of IFALD, principally due to improved lipid emulsion formulations and the multidisciplinary care of the patient with IF. As the recognition and treatment of IFALD continue to improve, the requirement of liver‐inclusive visceral grafts appears to be decreasing, representing a paradigm shift in the care of the patient with IF. This review highlights the current indications, graft selection, and outcomes of visceral transplantation for IFALD. Abstract : In this minireview, the authors describe how intestinal‐failure associated liver disease (IFALD) influences intestine transplant indications, graft selection, and outcomes, and why the recent dramatic improvement in the medical treatment of IFALD is changing the field of intestine transplantation.